Formative Assessment Strategies to Increase Student Participation and Motivation - Muafa, Ahsan; Lestariningsih, Wiji (Proceeding International Conference on Religion, Science and Education, 2025)
This study investigates the impact of formative assessment strategies on student engagement in higher education. Formative assessment, which involves continuous feedback and instructional adjustments based on student needs, has been shown to enhance engagement and learning motivation. Through survey methods and qualitative data analysis, this research found that the implementation of formative assessment significantly boosts active participation, critical thinking skills, and self-reflection among students. The findings indicate that students involved in formative assessment processes feel more engaged and motivated in their learning, which in turn improves their academic outcomes. These results underscore the importance of integrating formative assessment strategies into higher education curricula to enhance student engagement and learning outcomes.